Analysis of Thematic Progression in English of Economic Articles of Batamnews.com - Fitriana, Nur; Hendra Nugraha; Hilarius Raditya Priambada Purba (Universitas Cokroaminoto Palopo, 2025)
This study examines thematic progression patterns in English economic articles on Batamnews.com, focusing on how themes and rhemes are organized to ensure textual coherence and effectively convey economic information. Employing Halliday and Hasan’s functional approach, themes are categorized into topical, interpersonal, and textual types. The research adopts a qualitative method, analyzing the introduction sections of seven articles using systematic segmentation into clauses and classification of thematic progression patterns into re-iteration, zigzag, and multiple-theme patterns. The results reveal that the re-iteration pattern is the most frequently employed (28 instances), followed by the zigzag pattern (26 instances), and the multiple-theme pattern (7 instances). Thematic progression patterns significantly contribute to enhancing the coherence and clarity of the articles, allowing economic concepts to be effectively communicated. The findings underscore the strategic role of thematic organization in digital journalism, providing practical insights for journalists and scholars in understanding how economic information is structured and adapted for diverse audiences. This study contributes to linguistics and media studies by offering a deeper understanding of the interaction between thematic patterns and the communication of complex economic topics in the digital age.